Cells must express components of the planar cell polarity system and extracellular matrix to support cytonemes - Huang, Hai; Kornberg, Thomas B (eLife, 2016)
Drosophila dorsal air sac development depends on Decapentaplegic (Dpp) and Fibroblast growth factor (FGF) proteins produced by the wing imaginal disc and transported by cytonemes to the air sac primordium (ASP). Dpp and FGF signaling in the ASP was dependent on components of the planar cell polarity (PCP) system in the disc, and neither Dpp- nor FGF-receiving cytonemes extended over mutant disc cells that lacked them. ASP cytonemes normally navigate through extracellular matrix (ECM) composed of collagen, laminin, Dally and Dally-like (Dlp) proteins that are stratified in layers over the disc cells. However, ECM over PCP mutant cells had reduced levels of laminin, Dally and Dlp, and whereas Dpp-receiving ASP cytonemes navigated in the Dally layer and required Dally (but not Dlp), FGF-receiving ASP cytonemes navigated in the Dlp layer, requiring Dlp (but not Dally). These findings suggest that cytonemes interact directly and specifically with proteins in the stratified ECM.
Keywords: cytoneme; Heparan sulfate proteoglycan; planar cell polarity; extracellular matrix